Statement on biological security education to the Biological Weapons Convention - ninth preparatory committee on behalf of the Biological Security Research Centre, London Metropolitan University, UK - Crowley, Michael; Dando, Malcolm; Edwards, Brett; Novossiolova, Tatyana; Shang, Lijun; Whitby, Simon (2022)
This is a statement to the ninth preparatory committee of the Biological Weapons Convention, held at the Palais des Nations, United Nations Office at Geneva - on behalf of the Biological Security Research Centre, London Metropolitan University, UK on biological security education.